Keeping Sense Open Jean-Luc Nancy, Karl Rahner, and Bodies - Fritz, Peter Joseph 1981- (2016)
This article introduces the French philosopher Jean-Luc Nancy to theologians by placing him in critical dialogue with Karl Rahner. It examines how Nancy's deconstruction of Christianity accuses Western reason, including Christianity, of forgetting the body and supporting an ethos of disembodiment. Nancy proposes a new opening of reason (déclosion, "dis-closure") and a corresponding praxis ("adoration"). This reason and praxis involve an exit from Christianity. Rahnerian essays on matter, spirit, and sacramentality demonstrate that while Christianity has, historically, fallen prey to the pathologies Nancy identifies, it also has thought in terms of something like dis-closed reason and has practiced something like "adoration." While Nancy's insistence on the need for an exit from Christianity is not necessarily well posed, his deconstruction of Christianity can help Christian theologians as they develop thinking that supports an ethos sensitive to the body-or that keeps the body's sense open.
Keywords: Eucharist; Jean-Luc Nancy; Karl Rahner; Body; Deconstruction; Postmodern theology; Symbol